Calibrating page sized Gafchromic EBT3 films. Issue 1 (2nd January 2013) - Crijns, W.; Maes, F.; van der Heide, U. A.; Van den Heuvel, F.
Abstract : Purpose: : The purpose is the development of a novel calibration method for dosimetry with Gafchromic EBT3 films. The method should be applicable for pretreatment verification of volumetric modulated arc, and intensity modulated radiotherapy. Because the exposed area on film can be large for such treatments, lateral scan errors must be taken into account. The correction for the lateral scan effect is obtained from the calibration data itself. Methods: : In this work, the film measurements were modeled using their relative scan values (Transmittance, T ). Inside the transmittance domain a linear combination and a parabolic lateral scan correction described the observed transmittance values. The linear combination model, combined a monomer transmittance state ( T 0 ) and a polymer transmittance state ( T ∞ ) of the film. The dose domain was associated with the observed effects in the transmittance domain through a rational calibration function. On the calibration film only simple static fields were applied and page sized films were used for calibration and measurements (treatment verification). Four different calibration setups were considered and compared with respect to dose estimation accuracy. The first (I) used a calibration table from 32 regions of interest (ROIs) spread on 4 calibration films, the second (II) used 16 ROIs spread on 2 calibration films, the third (III), and fourth (IV) used 8 ROIs spread on a single calibration film. The calibration tables of the setups I, II, and IV contained eight dose levels delivered to different positions on the films, while for setup III only four dose levels were applied. Validation was performed by irradiating film strips with known doses at two different time points over the course of a week. Accuracy of the dose response and the lateral effect correction was estimated using the dose difference and the root mean squared error (RMSE), respectively. Results: : A calibration based on two films was the optimal balance between cost effectiveness and dosimetric accuracy. The validation resulted in dose errors of 1%–2% for the two different time points, with a maximal absolute dose error around 0.05 Gy. The lateral correction reduced the RMSE values on the sides of the film to the RMSE values at the center of the film. Conclusions: : EBT3 Gafchromic films were calibrated for large field dosimetry with a limited number of page sized films and simple static calibration fields. The transmittance was modeled as a linear combination of two transmittance states, and associated with dose using a rational calibration function. Additionally, the lateral scan effect was resolved in the calibration function itself. This allows the use of page sized films. Only two calibration films were required to estimate both the dose and the lateral response. The calibration films were used over the course of a week, with residual dose errors ⩽2% or ⩽0.05 Gy.